English in Science Education Significantly Enhances Student Achievement in Iraq: Bahasa Inggris dalam Pendidikan Sains Secara Signifikan Meningkatkan Prestasi Siswa di Irak - Ameen, Badr Jaafar (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The influence of teaching methods in science education is critical for student achievement, particularly in multilingual contexts. Specific Background: This study focuses on the Al-Mutamaizeen and Al-Mutafawqeen secondary schools in Iraq, where students study scientific subjects in English and Arabic, respectively. Knowledge Gap: Limited research exists on how language of instruction in scientific subjects impacts English language proficiency and overall academic achievement among high-achieving students. Aims: The research aimed to identify the effect of teaching scientific subjects in English on the academic achievement of students in the English language, comparing students from Al-Mutamaizeen (studying in English) with those from Al-Mutafawqeen (studying in Arabic). Results: The study employed an experimental design and included a sample of 76 students from Najaf High School for the Distinguished and 80 students from Kufa High School for the Gifted. Statistical analysis revealed significant differences in favor of the students who studied science subjects in English, attributing their success to the continuous use of English during scientific instruction. Novelty: This study provides novel insights into the direct relationship between language of instruction in science and English language proficiency, showing how integrating English into scientific subjects enhances overall academic performance. Implications: The findings suggest that teaching scientific subjects in English could be generalized to similar student groups to improve both English proficiency and academic achievement in science, particularly in multilingual settings. Highlughts: Language instruction influences student achievement in multilingual science education. English use in science improves language skills and academic performance. Teaching science in English benefits high-achieving students' overall achievement. Keywords: Teaching methods, English instruction, science education, academic achievement, multilingual schools.